2000
DOI: 10.1002/1521-4141(200006)30:6<1706::aid-immu1706>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Mannan-binding lectin and C1q bind to distinct structures and exert differential effects on macrophages

Abstract: While the interaction of complement component C1q with cellular proteins is extensively studied, much less is known about the binding of the structurally related molecule, mannan‐binding lectin (MBL) to various cells. Here we show by cytofluorimetry that the interaction of MBL with immunocompetent cells is much more restricted than that of C1q. It is shown that under conditions of physiological ionic strength MBL binds to human monocyte‐derived macrophages (Mϕ) and monocytoid cell lines, but not to T and B lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
(54 reference statements)
0
14
1
Order By: Relevance
“…These results might be surprising since C1q, as activator of the complement system, is mainly considered as a pro-inflammatory mediator. C1q induces production of pro-inflammatory cytokines [32,33] and complement proteins [34] and regulates the deposition of immune complexes [35]. These pro-inflammatory activities of C1q contrast with the observation that C1q deficiency in humans and in animals is associated with the development of the autoimmune disease SLE [26].…”
Section: Discussionmentioning
confidence: 99%
“…These results might be surprising since C1q, as activator of the complement system, is mainly considered as a pro-inflammatory mediator. C1q induces production of pro-inflammatory cytokines [32,33] and complement proteins [34] and regulates the deposition of immune complexes [35]. These pro-inflammatory activities of C1q contrast with the observation that C1q deficiency in humans and in animals is associated with the development of the autoimmune disease SLE [26].…”
Section: Discussionmentioning
confidence: 99%
“…The ligand binding assay was performed as described [57]. Washed imMDCs (2 × 10 5 ) were resuspended in Tris-buffered saline (pH7.4) containing 5 mM CaCl 2 , 1% bovine serum albumin (buffer A).…”
Section: Methodsmentioning
confidence: 99%
“…A dominant role of Fc γ RIII has been demonstrated in the induction of both TNF- α and IL-1- α production by human macrophages from patients with rheumatoid arthritis [147]. Macrophage production of C3 and C5 is increased through both the Fc [148, 149] and C1q receptors [150]. Gessner et al [148, 149] have found that production and cleavage of C5 by macrophages is regulated by Fc γ Rs.…”
Section: The Role Of Fcγrs In Cardiac Allograft Transplantation In VImentioning
confidence: 99%